The privatization of fraud investigation: internal investigations by fraud examiners - Gottschalk, Petter (Routledge, 2021)
This book discusses privatization of law enforcement in relation to suspected corporate crime and recommends guidelines for successful fraud examinations. There is a growing business for global auditing and local law firms to conduct internal investigations at client organizations when there is suspicion of white-collar misconduct and crime. This book reflects on the work by these private fraud examiners in terms of an evaluation of their investigation reports. The book brings an original theoretical and methodological approach to investigations of white-collar crime. It develops the theory of convenience as an explanation for motive, opportunity and willingness to commit and conceal white-collar crime. This theory is then related to the case studies. Structured in such a way as to allow the reader to use the text as a non-sequential reference source or guide to a set of connected issues, the book illustrates the practice of privatization by cases and presents guidelines for successful fraud examination. As an investigation can lead to conviction and incarceration, this privatization of crime investigation feeds into the larger issue of privatization of policing